THE INFLUENCE OF BRAND TRUST AND LIFESTYLE ON PURCHASING DECISIONS FOR POCARI SWEAT IN SURABAYA - Jonsen Sitohang; Hery Pudjoprastyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of brand trust and lifestyle on purchasing decisions for Pocari Sweat in Surabaya. The population in the study were Pocari Sweat consumers who live in Surabaya with a sample of 99 respondents. The sampling technique used was purposive sampling. The analysis method was carried out with Structural Equation Models (SEM) with the alternative Partial Least Sqaure (PLS) method. The results of this study are: 1) Brand trust has a positive and significant effect on purchasing decisions for Pocari Sweat in Surabaya 2) Lifestyle has a positive and significant effect on purchasing decisions in Surabaya.